アストカイロ(AST)気功が脳内出血に及ぼす治療効果 - 佐野, 紀江; 鈴木, 正弘; 北村, 幸郷; 小鳥, 一詔 (人体科学, 2003)
AST chiro Qi-gong has been reported on several disease by clinical and basic medical stance. Authors reported about the clinical effects on brain hemorrhage of two patients. After therapy, physical examination and laboratory data showed the effects for recovery from hemorrhage and its complication. Because AST therapy could start from the early time just after the onset of the attack the patients could recover soon. Moreover, the therapy itself provide patients with a peace of mind. AST therapy could be thought to be useful for Brain hemorrhage.